Relaxation measurements in the regime of the second magnetization peak in Nb films - Stamopoulos, D.; Niarchos, D. (PHYSICA C-SUPERCONDUCTIVITY AND ITS APPLICATIONS, 2004)
We report on magnetic measurements as a function of field, temperature and time (relaxation) in superconducting Nb films of critical temperature T-c = 9.25 K. The magnetic measurements as a function of field exhibited a "second magnetization peak" (SMP) which in general is accompanied by thermomagnetic instabilities (TMIs). The lines H-smp(T) where the SMP occurs and the H-fj(T) where the first flux jump in the virgin magnetization curves is observed, end at a characteristic point (T-0, H-0) approximate to (7.2K, 80 Oe). Relaxation measurements showed that for T < T-0 approximate to 7.2 K the activation energy U-0 and the normalized relaxation rate S exhibit non-monotonic behavior as a function either of temperature or field. The extrema observed in U-0 and S coincide with the points H-on(T) or H-smp(T) of the SMP. In the regime T > T-0 approximate to 7.2 K both U-0 and S present a conventional monotonic behavior. These results indicate that the SMP behavior observed in Our Nb films is promoted by the anomalous relaxation of the magnetization. (C) 2004 Elsevier B.V. All rights reserved.